The Relationship Between Cognitive Dysfunction and Symptom Dimensions Across Schizophrenia, Bipolar Disorder, and Major Depressive Disorder - Zhu, Yue; Womer, Fay Y.; Leng, Haixia; Chang, Miao; Yin, Zhiyang; Wei, Yange; Zhou, Qian; Fu, Shinan; Deng, Xin; Lv, Jing; Song, Yanzhuo; Ma, Yinzhu; et al. (Frontiers in Psychiatry, 2019)
Background: Cognitive dysfunction is considered a core feature among schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MDD). Despite a copious literature on comparisons of cognitive dysfunction in these disorders, the relationship between cognitive dysfunction and symptom dimensions remains unclear. The study aims to examine the relationship between cognitive impairment and psychopathology in SZ, BD, and MDD. Methods: A total of 716 participants (262 patients with SZ, 104 patients with BD, 101 patients with MDD, and 249 healthy controls) were assessed using the MATRICS Consensus Cognitive Battery (MCCB), Wisconsin Card Sorting Test (WCST), and the Brief Psychiatric Rating Scale (BPRS). Results: We found cognitive dysfunction in all of the participant groups with psychiatric disorders. Negative/disorganized symptoms were the most strongly associated with cognitive dysfunctions across SZ, BD, and MDD. Conclusions: The severity of cognitive deficits correlates with the severity of negative/disorganized symptoms across SZ, BD, and MDD. Our findings suggest that the severity of cognitive deficits co-varies in accordance with the severity of certain dimensions of psychopathology, especially negative/disorganized symptom and that negative/disorganized symptoms may be important targets in cognitive remediation for SZ, BD, and MDD.